Explosion systems with inert high modulus components : increasing the efficiency of blast technologies and their applications /: increasing the efficiency of blast technologies and their applications. (2019) - Balagansky, I. A (Igor Andreevich), 1952-; Bataev, A. A (Anatoliy); Bataev, I. A (Ivan)
No abstract available